Body mass index impacts the choice of lipid‐lowering treatment with no correlation to blood cholesterol – Findings from 52 916 patients in the Dyslipidemia International Study (DYSIS). Issue 11 (10th July 2018) - Ferrières, Jean; Lautsch, Dominik; Gitt, Anselm K.; De Ferrari, Gaetano; Toplak, Hermann; Elisaf, Moses; Drexel, Heinz; Horack, Martin; Baxter, Carl; Ambegaonkar, Baishali; Brudi, Philippe; Toth, Peter P.
Abstract : A high body mass index (BMI) is associated with increased cardiovascular risk. We sought to identify whether BMI influences the choice of lipid‐lowering treatment in a large, real‐world cohort of 52 916 patients treated with statins. The Dyslipidemia International Study (DYSIS) is a cross‐sectional, observational, multicentre study in statin‐treated patients ≥45 years of age from 30 countries; 1.1% were underweight (BMI < 18.5 kg/m 2 ), 33.1% had normal weight (BMI 18.5‐24.9 kg/m 2 ), 41.5% were overweight (BMI 25‐29.9 kg/m 2 ), 17.1% had class I obesity (BMI 30.0‐34.9 kg/m 2 ), 5.0% had class II obesity (BMI 35‐39.9 kg/m 2 ), and 2.1% had class III obesity (≥40 kg/m 2 ). BMI correlated with high‐density lipoprotein cholesterol (HDL‐C) and triglycerides (Spearman's ρ: −0.147 and 0.170, respectively; P < 0.0001 for both); however, there was no correlation with low‐density lipoprotein cholesterol (LDL‐C; ρ: 0.003; P = 0.51). Statin intensity increased with increasing BMI (ρ: 0.13; P < 0.001), an association that held after adjustment for comorbidities (OR: 2.4; 95% CI: 2.0‐3.0) on BMI ≥ 30 kg/m 2 for atorvastatin equivalent ≥40 mg/d.